PEMBERANTASAN KORUPSI MENURUT FIQH SIYASAH - Fitri Rahma Yani; Muhammad Pryambudi; Sherly Syafira; Yesinta; Zulfahri (JOURNAL SAINS STUDENT RESEARCH, 2023)
Corruption is a serious problem facing the global community, including Indonesia, which has the potential to hinder development progress and social welfare. Therefore, efforts to eradicate corruption are essential. In this context, fiqh siyasah as a branch of Islamic jurisprudence that focuses on public law and governance provides a relevant and in-depth view of this issue. Fiqh siyasah rejects all forms of corruption, in line with the basic principles of Islam that emphasize justice and openness. In addition, fiqh siyasah emphasizes the importance of accountability and transparency in the government structure, including the use of public funds, the appointment of officials, and the implementation of policies and laws. This study aims to evaluate the anti-corruption strategies that are sourced from the principles of fiqh siyasah. The research method used is qualitative with a normative approach. The results of this study highlight that fiqh siyasah provides a number of comprehensive and sustainable strategies in combating corruption, including: increasing public awareness of the risks of corruption, enforcing the law firmly and fairly, strengthening transparency and accountability in governance, and creating a healthy economic environment. It is hoped that these strategies can be an effective solution in tackling corruption in Indonesia.